Neurotoxicity of Star Anise Tea - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Seven cases of adverse neurologic reactions associated with the home administration of star anise tea to young infants, aged 2 to 12 weeks, and identified over a 2-year period, are reported from the Miami Children's Hospital, FL.